Aggregation Induced Enhancement of Linear and Nonlinear Optical Emission from a Hexaphenylene Derivative. (8th August 2016) - Duan, Yulong; Ju, Chenggong; Yang, Guang; Fron, Eduard; Coutino‐Gonzalez, Eduardo; Semin, Sergey; Fan, Chencheng; Balok, Ryan S.; Cremers, Jonathan; Tinnemans, Paul; Feng, Yaqing; Li, Yuliang; et al.
Abstract : The discovery of the phenomenon known as aggregation‐induced emission (AIE) has opened the door to a variety of brilliant organic solid‐state light‐emitting materials. While AIE is well established in linear optics, the development of AIE luminogens (AIEgens) with highly efficient nonlinear optical (NLO) effects remains relatively unexplored. Particularly, second‐order NLO requires the AIEgens to be organized in a non‐centrosymmetric fashion, and such examples are rarely reported. Here, an AIEgen, 2, 7‐di([1, 1′‐biphenyl]‐4‐yl)‐fluorenone (4‐DBpFO), is designed and synthesized by introducing a carbonyl group onto the backbone of p ‐hexaphenylene. The restricted rotation of the compound upon aggregation results in a dramatic enhancement of the linear optical emission when forming self‐assemblies. Furthermore, introducing the carbonyl group drives the formation of hydrogen bonded molecular chains, which are attached by the zigzag CH⋅⋅⋅π interactions in a non‐centrosymmetric way. As a result, the dipole of each individual molecule contributes accumulatively to a macroscopic dipole of the formed 4‐DBpFO microcrystals. This leads to a highly efficient second harmonic generation with very high laser damage treshold. This AIEgen, whose optical response is greatly enhanced in both linear and nonlinear optical regimes upon the formation of well‐defined self‐assemblies, has potential applications in next generation photonic circuits. Abstract : An aggregation‐induced emission luminogen active in both linear and nonlinear optics is designed and synthesized based on the p ‐hexaphenylene backbone. The self‐assembled microstructures demonstrate a linear optical quantum efficiency of about ten times higher than that of the solution state, and a highly efficient and stable second harmonic generation signal greater than that of lithium niobate.